OECD COMPARATIVE ECONOMIC GROWTH 1950–1985: CATCH-UP AND CONVERGENCE - Dowrick, Stephen; Nguyen, Dinh Trung (American Economic Review, 1989)
The apparent convergence of OECD income levels since 1950 is subjected to rigorous testing that suggests that there has occurred a systematic process of catching up in levels of total factor productivity. An econometric model of relative economic growth exhibits parameter stability over three decades, including the period after 1973, and statistical robustness, particularly with respect to sample selection. A reassessment is made of OECD comparative economic growth performance. Copyright 1989 by American Economic Association.